Gene targeting technologies in rats: Zinc finger nucleases, transcription activator‐like effector nucleases, and clustered regularly interspaced short palindromic repeats. (27th December 2013) - Mashimo, Tomoji
<x xml:space="preserve">Abstract</x> The laboratory rat has been widely used as an animal model in biomedical science for more than 150 years. Applying zinc‐finger nucleases or transcription activator‐like effector nucleases to rat embryos via microinjection is an efficient genome editing tool for generating targeted knockout rats. Recently, clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated endonucleases have been used as an effective tool for precise and multiplex genome editing in mice and rats. In this review, the advantages and disadvantages of these site‐specific nuclease technologies for genetic analysis and manipulation in rats are discussed.